A partially inactivating mutation in the sodium-dependent lysophosphatidylcholine transporter MFSD2A causes a non-lethal microcephaly syndrome - Alakbarzade, Vafa; Hameed, Abdul; Quek, Debra Q Y; Chioza, Barry A; Baple, Emma L; Cazenave-Gassiot, Amaury; Nguyen, Long N; Wenk, Markus R; Ahmad, Arshia Q; Sreekantan-Nair, Ajith; Weedon, Michael N; Rich, Phil; et al. (Nature genetics, 2015)
Andrew Crosby, David Silver and colleagues show that a partially inactivating mutation in MFSD2A causes a non-lethal microcephaly syndrome with symptoms that include intellectual disability, spasticity and absent speech. Their findings indicate an essential role for lysophosphatidylcholine uptake in human brain development and function. The major pathway by which the brain obtains essential omega-3 fatty acids from the circulation is through a sodium-dependent lysophosphatidylcholine (LPC) transporter (MFSD2A), expressed in the endothelium of the blood-brain barrier. Here we show that a homozygous mutation affecting a highly conserved MFSD2A residue (p.Ser339Leu) is associated with a progressive microcephaly syndrome characterized by intellectual disability, spasticity and absent speech. We show that the p.Ser339Leu alteration does not affect protein or cell surface expression but rather significantly reduces, although not completely abolishes, transporter activity. Notably, affected individuals displayed significantly increased plasma concentrations of LPCs containing mono- and polyunsaturated fatty acyl chains, indicative of reduced brain uptake, confirming the specificity of MFSD2A for LPCs having mono- and polyunsaturated fatty acyl chains. Together, these findings indicate an essential role for LPCs in human brain development and function and provide the first description of disease associated with aberrant brain LPC transport in humans.